TOWARDS A COOPERATIVE RURAL DEVELOPMENT INFORMATION NETWORK (COORDINET) IN INDIA - Raju, K.A.; Karisiddappa, C.R. (Malaysian Journal of Library and Information Science, 2000)
The paper takes cognisance of the attempts made by the National Institute of Rural Development (NIRD), the apex research and training institution in rural development in India, to conceive a Cooperative Rural Development Information Network (COORDINET). The functions of the Network and how it can help in strengthening the development of skills, the design of appropriate of information products, exchange of information and document supply is described.